A bibliometric analysis of research on Technological Pedagogical Content Knowledge on in-service teachers in higher education - Yang, Mingxing; Jeyaraj, Joanna Joseph; Ahmad, Norhakimah Khaiessa; Yang, Wei (Dr. Khairi Obaid Tayyeh Al-Zubaid, 2024)
Technological Pedagogical Content Knowledge illustrates the interconnected nature of knowledge required to effectively integrate technology in enhancing student learning. While numerous review studies on Technological Pedagogical Content Knowledge exist, those that employ a bibliometric analysis are limited. In this comprehensive bibliometric review, we analyzed 209 Technological Pedagogical Content Knowledge studies focusing on in-service teachers in higher education, sourced from the Scopus database from 2012 through April 2023. The significance of this study lies in its effort to map the research landscape of Technological Pedagogical Content Knowledge by addressing the main question: What are the primary trends, key contributors, thematic areas, and keyword co-occurrence networks in Technological Pedagogical Content Knowledge research on in-service teachers in higher education? We adopted PRISMA guidelines into the standard bibliometric workflow and used VOSviewer as the visualization tool. Publication trends, major contributors, research areas, and keyword co-occurrence networks were identified. The analysis indicated an increasing trend in the number of publications on in-service teachers' Technological Pedagogical Content Knowledge in higher education, with the highest number recorded in 2022. We also identified representative articles, institutions, the most contributing journals, and funding agencies, most from developed countries/regions. The analysis highlights prolific researchers, key research areas, and keyword co-occurrence networks. Overall, this analysis has provided a comprehensive overview of the current research in higher education. Based on these findings, we recommend that future research focus on Technological Pedagogical Content Knowledge training modules and AI-based Technological Pedagogical Content Knowledge frameworks for teachers in higher education.